Urban areas and global climate change - Holt, William G. (Emerald, 2012)
Examining urban environmental issues at the macro, municipal level down to the micro community and individual level, this volume features cities and metropolitan regions across the global north and south with case studies from the United States, Canada, Eastern and Western Europe to India, Central America, South America and Africa. Contributions on the global north examine: the role of governing processes in sustainable cities; local growth machines and their carbon consequences; tackling climate change adaptation through community participation; climate protection and the participation and engagement of citizens; the importance of networking; and assessing the success of the environmental justice within emissions trading schemes. Case studies on the global south look at such topics as: how resource-constraints shape climate adaptation; the emergence of low-carbon development; urban vulnerability and adaptation to the health impacts of air pollution and climate extremes; global environmental changes and impacts on fishing activities; environmental justice and the social construction of space in urban poor communities; and the inverse connection between gender and climate change.
Keywords: Social Science -- Sociology -- General.; Social Science -- General.; Urban communities.; Global warming.; Urban ecology (Sociology); Climatic changes.; elektronické knihy; electronic books